2018
DOI: 10.1186/s40563-018-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of technological procedures on mechanical properties of bonded joint

Abstract: Facades are a key element in creating modern building designs. Their area is up to ¾ of the total area of the outer surface, and this also largely influences the interior of the building. The choice of the type of sheathing structure is not only dependent on the appearance or requirements of the indoor environment but also on the maintenance, the lifetime of the structure and the assembly technology. Ventilated facades, known as "Cold Facades", are an appropriate solution. The principle of these structures is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…The study raises the issue of pull-off measurement reliability as its results infl uence decisions on how to repair the facade (46). Due to the observed variability related to the adhesion measurement, conclusions to modify the current model of assessment of construction products using this essential characteristic (35,41), in conjunction with another product feature, were formulated (30,35,41,50). It is also important because the method of measuring adhesion is destructive.…”
Section: Results and Their Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The study raises the issue of pull-off measurement reliability as its results infl uence decisions on how to repair the facade (46). Due to the observed variability related to the adhesion measurement, conclusions to modify the current model of assessment of construction products using this essential characteristic (35,41), in conjunction with another product feature, were formulated (30,35,41,50). It is also important because the method of measuring adhesion is destructive.…”
Section: Results and Their Analysismentioning
confidence: 99%
“…The literature also provides information that the sample preparation procedure infl uences the measured value of adhesion (50).…”
Section: Results and Their Analysismentioning
confidence: 99%
“…The effect of manufacturing imperfections, surface defects and their combinations has already been tested by the authors on the sintered ceramic substrate in 2018; 20 therefore, some of the presented results will be compared also with this part of the research. The ceramic tile used was a non-porous material, thus a little different behaviour was expected from timber substrate.…”
Section: Resultsmentioning
confidence: 99%
“…When testing the influence of this group on ceramic substrate, the bond strength rate was reduced by only 3%. 20 It was observed that the contaminated surface prevented the adhesive from penetrating the substrate, since the fine particles of the sawdust formed a thin separation layer. In II group, as already mentioned above, the greatest decrease in bond strength was monitored in the 14th combination, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation